Aberrant G-protein coupled hormone receptor in adrenal diseases. Issue 2 (April 2018) - St-Jean, Matthieu; Ghorayeb, Nada El; Bourdeau, Isabelle; Lacroix, André
Abstract : The regulation of cortisol or aldosterone production when ACTH of pituitary origin or the renin-angiotensin systems are suppressed in primary adrenal Cushing's syndrome or in primary aldosteronism is exerted by diverse genetic and molecular mechanisms. In addition to recently identified mutations in various genes implicated in the cyclic AMP or ion channel pathways, steroidogenesis is not really autonomous as it is frequently regulated by the aberrant adrenocortical expression of diverse hormone receptors, particularly G-protein coupled hormone receptors (GPCR) which can substitute for the normal function of ACTH or angiotensin-II. In addition, paracrine or autocrine production of ligands for the aberrant GPCR such as ACTH or serotonin is found in some adrenal tumors or hyperplasias and participates in a complex regulatory loop causing steroid excess. Targeted therapies to block the aberrant ligands or their receptors could become useful in the future, particularly for patients with bilateral source of steroid excess.